Dance as artistic leisure and mental health promotion: a cross-sectional study of psychological outcomes across dance styles - Aglaia Zafeiroudi; Dimitrios Goulimaris; Ioannis Trigonis; Ioannis Tsartsapakis; Vasileios Papacharisis; Theodora Tseligka; Charilaos Kouthouris (BMC Psychology, 2026)
Abstract Background Dance, as a creative and embodied form of physical activity, has been associated with psychological well-being. However, limited research has examined how recreational dance participation is related to mindfulness, self-compassion, and life satisfaction in non-clinical populations. This study aimed to address this gap by comparing psychological outcomes between recreational dancers and non-dancers and by examining dance-related characteristics among dancers. Methods A cross-sectional design was used with 1,335 participants, including 912 recreational dancers from various styles (ballet, tango, Latin, modern/contemporary, traditional, aerial, and dance aerobic) and 423 non-dancers as a comparison group. Participants completed Mindful Attention Awareness Scale (MAAS), the Self-Compassion Scale (SCS), and the Satisfaction with Life Scale (SWLS). Statistical analyses included correlations, multivariate analysis of variance (MANOVA), analysis of covariance (ANCOVA controlling for age and gender), and cluster analysis. Results Recreational dancers reported significantly higher levels of mindfulness, self-compassion, and life satisfaction than non-dancers, and the three psychological variables were positively correlated. Among dancers, differences across dance styles appeared mainly for mindfulness, with tango dancers showing the highest mindfulness scores. Self-compassion showed a more complex pattern and appeared to vary according to age-related differences in the adjusted analyses, while life satisfaction did not differ significantly by dance style. Years of dance participation was not significantly associated with the psychological outcomes, while frequency of dance participation showed limited and inconsistent associations. A small gender-related difference was also observed, with female participants reporting higher life satisfaction than male participants. Mindfulness-based profiles further showed that dancers with higher mindfulness also reported higher self-compassion and life satisfaction. Conclusions Recreational dance participation was associated with higher levels of mindfulness, self-compassion, and life satisfaction, and may reflect a meaningful embodied, expressive, and socially situated leisure activity. These cross-sectional findings highlight the relevance of recreational dance to psychological well-being in non-clinical populations and may have implications for dance education, community leisure programs, and health-promotion initiatives that emphasize mindfulness, self-acceptance, emotional expression, and supportive teaching environments. Further longitudinal, intervention-based, and active-comparison studies are needed to better clarify these associations.